The relationship between family support and the quality of life of patients with seroconcordant HIV at the Pandian health center and Pamolokan health center, Sumenep Regency - Fikri, M.Kep, Zahid; Dwi Kurnia, Anggraini; Sunardi, Sunardi; Arfianto, Muhammad Ari; ‘Ibad, Muhammad Rosyidul; Kholis, Moh. Agung Nur; Mu'jizah, Khikmatul; Toonsiri, Chanandchidadussadee; Wijaya Ridi Putra, Kusuma (University of Muhammadiyah Malang, 2023)
Introductions: The HIV/AIDS endemic infected millions worldwide in 2019. Indonesia reported a very significant case of the disease, where East Java occupies the fourth position out of all the provinces. People who suffer from this disease (ODHA) are often associated with a poor quality of life. Family support is needed to control the patient's disease and improve the patient's quality of life. Objectives: This study aims to determine the relationship between family support and the quality of life of seroconcordant HIV patients. Methods: The study design used cross-sectional with a sample of 36 seroconcordant PLHIV patients and 32 people who met the inclusion criteria (living with family, married, and registered at the Sumenep District Health Center). The data collection instrument used the